Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Formation de l'État et politiques sociales aux Etats-Unis - Skocpol, Theda (Actes de la recherche en sciences sociales, 1993)
Les Américains éprouvent une certaine méfiance à l'égard de la puissance de l'Etat. Cependant, si l'on analyse l'histoire du développement du pays, on constate que les Etats-Unis ont toujours eu "un Etat". Les changements qui ont affecté l'Etat américain -passé d'un Etat fédéral, non bureaucratique, "Etat de tribunaux et de partis" au XIXe siècle, à un Etat fédéral, partiellement partiellement bureaucratisé, orienté vers l'action en faveur de groupes d'intérêts particuliers au XXe siècle -permettent de comprendre les différentes phases et les modalités de la politique sociale américaine. Les Etats-Unis n'ont pas développé un Etat-providence qui, comme en Europe, assure la protection sociale des ouvriers et de tous les citoyens. Entre 1870 et 1920, la politique sociale des Etats-Unis s'est développée principalement en faveur des anciens combattants et des mères de famille ; après 1930, elle a porté surtout sur la mise en place d'un système d'assurance vieillesse pour les retraités. Les institutions politiques américaines ont favorisé le développement de dépenses sociales importantes pour des groupes sociaux qui ne sont pas les plus démunis.
Keywords: 1800-1899; 1900-1999; amériques; cours; discipline; his4443; histoire et politique; maternité; politique américaine; politiques publiques; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; thématiques; états-unis